(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The increase in drug resistant TB demands accurate and timely clinical approach. This study compared the first and second power anti-TB drugs to detect resistance to phenotypic, genotypic assays. Genotypic tests offered rapid results, while phenotypic methods covered wide profiles. Among the isolates, there were 37 MDRs and 1 XDR. Conclusions emphasize a combination of clinical methods for early identification and improvement of TB control, especially in resource-limited settings.